Determining the Matrilineal Origin of Indonesian Kerinci Duck Breed (Anas platyrhynchos) Based on MT-ND2 Gene Diversity - Depison; Putra, Widya Pintaka Bayu; Gushairiyanto; Gunawan, Asep; Sumantri, Cece (HAYATI Journal of Biosciences, 2024)
The Kerinci duck (Anas platyrhynchos), hailing from Jambi Province, represents one of the local duck breeds of Indonesia. This study aimed to ascertain the matrilineal origin of Kerinci ducks through analysis of the mitochondrial NADH Dehydrogenase subunit 2 (MT-ND2) gene. In this pursuit, forward sequences of the MT-ND2 gene (490 bp) were extracted from unsexed Kerinci ducks, totalling forty-eight (48) sequences, procured from blood samples. The findings demonstrated the identification of fifteen (15) distinct haplotypes within the MT-ND2 gene, with corresponding haplotype diversity (Hd) and nucleotide diversity (pi) values of 0.74 and 0.003, respectively. The resulting phylogenetic tree unveiled that Kerinci ducks exhibit two matrilineal origins: an Asian and an independent Kerinci lineage. Moreover, most Kerinci ducks were categorised within the H4 group (24 birds) of the Asian lineage. Nevertheless, this study also revealed the existence of an independent Kerinci lineage comprising eight (8) duck haplotypes. In conclusion, the analysis of the MT-ND2 gene underscored the genetic introgression of A. zonorhyncha and A. poecilorhyncha in Kerinci ducks.